Effect of hot isostatic pressing on microstructure and mechanical properties of Ti6Al4V-zirconia nanocomposites processed by laser-powder bed fusion. (February 2022) - Hattal, Amine; Mukhtarova, Kamilla; Djemai, Madjid; Chauveau, Thierry; Hocini, Azziz; Fouchet, Jean Jacques; Bacroix, Brigitte; Gubicza, Jenő; Dirras, Guy
Graphical abstract: Highlights: HIP post-treatment was performed on L-PBF fabricated Ti64 reinforced with nYSZ ceramic. HIP post-treatment was successful in increasing the relative density of reinforced parts. HIP processing parameters prevented β phase formation in reinforced parts. HIP post-treatment generated thick α grains and homogeneous microstructure. HIP post-treatment increased the plastic deformation of all parts without drastic strength decrease. Abstract: This study discusses the effects of hot isostatic pressing (HIP) post-treatment on Laser Powder Bed Fusion of Ti6Al4V and Ti6Al4V reinforced with 1 wt% and 2.5 wt% of nano-yttria-stabilized zirconia (nYSZ). The bulk parts display a higher density after HIP post-treatment than the as-built counterparts. Besides, X-ray diffraction (XRD) analysis indicates a reduction of the β phase percentage after HIP. An increase in α grain thickness is noticed on both reinforced and unreinforced parts. Additionally, compared to their un-HIPed counterparts, the microhardness decreases after HIP post-treatment by 3%, 11%, 8% and 4% for the as-built Ti6Al4V, stress relieved Ti6Al4V, 1 wt% nYSZ reinforced and 2.5 wt% nYSZ reinforced parts, respectively. The same trend was observed for the yield stress, which decreases by 1%, 4% and 8%, for the as-built Ti6Al4V, stress relieved Ti6Al4V and 2.5 wt% nYSZ-reinforced parts respectively after HIP post-treatment, except for 1 wt% nYSZ-reinforced part, whose yield stress increase by about 7%, which could be attributed to the specific texture evolution within this material. The plastic strain was significantly enhanced after HIP in all materials.